Crystal Structure and Characterization of Two Layered Copper(II) Coordination Polymers with Anions of 3‐Phosphonopropionic Acid and (RS)‐2‐Phosphonobutyric Acid - Köferstein, Roberto; Arnold, Michael; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2018)
Blue single crystals of Cu[μ3‐O3P(CH2)2COOH]·2H2O (1) and Cu[(RS)‐μ3‐O3PCH(C2H5)COOH]·3H2O (2) were prepared in aqueous solutions (pH = 2.5–3.5). 1 crystallizes in space group Pbca (no. 61) with a = 812.5(2), b = 919.00(9), and c = 2102.3(2) pm. Cu2+ is fivefold coordinated by three oxygen atoms stemming from [O3P(CH2)2COOH]2– anions and two water molecules. The Cu–O bond lengths range from 194.0(3) to 231.8(4) pm. The connection between the [O3P(CH2)2COOH]2– anions and the Cu2+ cations yields a polymeric structure with layers parallel to (001). The layers are linked by hydrogen bonds. 2 crystallizes in space group Pbca (no. 61) with a = 1007.17(14), b = 961.2(3), c = 2180.9(4) pm. The copper cations are surrounded by five oxygen atoms in a square pyramidal fashion with Cu–O bonds between 193.6(4) and 236.9(4) pm. The coordination between [O3PCH(C2H5)COOH]2– and Cu2+ results in infinite puckered layers parallel to (001). The layers are not connected by any hydrogen bonds. Each layer contains both R and S isomers of the [O3PCH(C2H5)COOH]2– dianion. Water molecules not bound to Cu2+ are intercalated between the layers. UV/Vis spectra suggest three d–d transition bands at 743, 892, 1016 nm for 1 and four bands at 741, 838, 957, and 1151 nm for 2, respectively. Magnetic measurements suggest a weak antiferromagnetic coupling between Cu2+ due to a super‐superexchange interaction. Thermoanalytical investigations in air show that the compounds are stable up to 95 °C (1) and 65 °C (2), respectively.